An automated monitoring and environmental control system for laboratory-scale cultivation of oyster mushrooms using the Internet of Agricultural Thing (IoAT) - Islam, Md. Ariful; Islam, Md. Antonin; Miah, M. Saef Ullah; Bhowmik, Abhijit (Association for Computing Machinery, 2022)
This research paper presents an automated system for controlling and monitoring the cultivation of oyster mushrooms in a laboratory facility. The system uses an Internet of Things (IoT) based approach to automate the entire process. The main objective of this system is to make indoor mushroom cultivation easier and cost effective. The proposed system has proved to be very effective in saving labor cost by automatically monitoring and controlling the environment. Moreover, the proposed system has a real time update and monitoring feature which helps the grower to take immediate action. This paper provides a detailed insight into the project, including the development process, automation system, hardware setup, technical specifications, and results achieved after successful implementation.